PENERAPAN STRATEGI PEMBELAJARAN REMBUK AHLI PADA PROGRAM KESETARAAN - Agung Puji Hartoyo (Jurnal Ilmiah Visi, 2009)
Of the opinion that one of the crucial problems in improving the quality of equivalency education is related to the instructional strategy, this article focuses the discussion on the cooperative learning with expert discusson model as an alternative solution. Beside elaborating the procedures and techniques of implementing this instructional strategy as from planning through evaluation, it is believed that this strategy can be applied in conducting the programs of Package A, B, and C. The ideas proposed are expected to be useful for the teachers and tutors to improve the quality of equivqlency education in Indonesia. This strategy is also an answer to achieve instructional process standard of equivalency education as required in the National Education Minister’s Degree of No. 3 in 2008.